Practical Opportunities for Biopsychosocial Education Through Strategic Interprofessional Experiences in Integrated Primary Care - Funderburk, Jennifer S.; Gass, Julie; Shepardson, Robyn L.; Mitzel, Luke D.; Buckheit, Katherine A. (Frontiers in Psychiatry, 2021)
Even with the expansion of primary care teams to include behavioral health and other providers from a range of disciplines, providers are regularly challenged to deliver care that adequately addresses the complex array of biopsychosocial factors underlying the patient’s presenting concern. The limits of expertise, the ever-changing shifts in evidence-based practices, and the difficulties of interprofessional teamwork contribute to the challenge. In this article, we discuss the opportunity to leverage the interprofessional team-based care activities within integrated primary care settings as interactive educational opportunities to build competencies in biopsychosocial care among primary care team members. We argue that this approach to learning while providing direct patient care not only facilitates new provider knowledge and skills, but also provides a venue to enhance team processes that are key to delivering integrated biopsychosocial care to patients. We provide three case examples of how to utilize strategic planning within specific team-based care activities common in integrated primary care settings—shared medical appointments, conjoint appointments, and team huddles—to facilitate educational objectives.